Key elements in the quality assessment of a type 3 medication review - Robberechts, Anneleen; Michielsen, Melissa; Steurbaut, Stephane; De Meyer, Guido R. Y.; De Loof, Hans (Frontiers in Pharmacology, 2023)
Background: Medication reviews are a structured evaluation of a patient’s pharmacotherapy with the aim of optimizing medicines use and improving health outcomes. This entails detecting drug related problems and recommending interventions. A high level of quality is essential for the successful implementation of this service in community pharmacies but currently there is no instrument or tool to assess that overall quality. Aim: This study investigated the development of quality criteria of type 3 medication reviews (MR3s). Methods: After surveying the literature, an electronic questionnaire was developed to gather information about quality criteria for MR3. This survey, in Dutch, was distributed electronically. Four groups were queried: 1) pharmacists, mainly working in the Netherlands, involved in practice research and contacted through the PRISMA (Practice Research In Collaboration With Pharmacists) foundation, 2) Belgian pharmacy academics and pharmacists active in professional associations (APA), 3) Belgian pharmacists trained in medication review (MR) by the Royal Pharmacists Association of Antwerp (KAVA) and 4) Belgian pharmacy students. The survey included 57 criteria, divided into eight domains, which were ranked according to their importance by the participants. The results were analyzed statistically using the nonparametric Kruskal–Wallis test. Results: The survey was completed by 95 participants, including 42 PRISMA pharmacists, 19 APA pharmacists, 18 KAVA pharmacists and 16 pharmacy students. Opinions from participants from the different groups overlapped significantly. The use of simple and understandable language in the conversation with the patient was considered essential by the majority. Discussing the usefulness and purpose of a MR3 with the patient was also rated highly by all groups. Differences of opinion were present in aspects about laboratory values, the use of specific tools, and reporting to and consultation with the treating physician. The participants themselves formulated a limited number of additional assessment criteria. Conclusion: There was widespread agreement on the hierarchy of the quality assessment criteria for MR3s. Minor differences were related to the experience of the participants. With these results and a small number of suggested extra criteria, a quality assessment instrument for MR3 can be created.